Modified Nonradial Supper Efficiency Models - H. Jahanshahloo; F. Hosseinzadeh Lotfi; M. Khodabakhshi (Journal of Applied Mathematics)
Ranking Efficient Decision Making Units (DMUs) are an important issue in Data Envelopment Analysis (DEA). This is one of the main areas for the researcher. Different methods for this purpose have been suggested. Appearing nonzero slack in optimal solution makes the method problematic. In this paper, we modify the nonradial supper efficiency model to remove this difficulty. Some numerical examples are solved by modified model.